PENGARUH DANA OTONOMI KHUSUS TERHADAP KESEJAHTERAAN MASYARAKAT DI PROVINSI ACEH - Teuku Khairil Amal; Zulkifli Zulkifli; Eddy Gunawan (Fakultas Ekonomi dan Bisnis UNSYIAH, 2023)
AbstractThe purpose of this study is to determine the effect of special autonomy funds on the welfare of the people in Aceh Province. This study uses a description method, the data used are secondary data sourced from the Central Statistics Agency, Scientific Journals, and other secondary data sources. The variables used in researching welfare are education, health, and poverty data. The results of research in Aceh Province show that the special autonomy funds provided by the central government have not been able to prosper the people in Aceh Province. The central government and the provincial government of Aceh need to review the priorities of this special autonomy fund to improve the welfare of the people of Aceh province.Keywords: Special Autonomy Fund and Welfare.